2023
DOI: 10.3390/ijms24032203
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Sex Hormone Exposure Is Associated with the Development of Autism Spectrum Disorder

Abstract: Sexual differentiation is a major developmental process. Sex differences resulting from sexual differentiation have attracted the attention of researchers. Unraveling what contributes to and underlies sex differences will provide valuable insights into the development of neurodevelopmental disorders that exhibit sex biases. Autism spectrum disorder (ASD) is a neurodevelopmental disorder that affects an individual’s social interaction and communication abilities, and its male preponderance has been consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…In this review, we discussed neuroinflammation and oxidative stress as risk factors in the pathogenesis of ASD. The prenatal environment is not only a sensitive period for fetal development but also a vulnerable period for the onset of disorders such as NDDs and psychiatric disorders [ 9 , 10 , 11 , 192 ]. MIA, one of the environmental factors involved in the onset of ASD, induces neuroinflammation and oxidative stress in the offspring and directly or indirectly damages the placenta and fetal brain during embryonic stages ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we discussed neuroinflammation and oxidative stress as risk factors in the pathogenesis of ASD. The prenatal environment is not only a sensitive period for fetal development but also a vulnerable period for the onset of disorders such as NDDs and psychiatric disorders [ 9 , 10 , 11 , 192 ]. MIA, one of the environmental factors involved in the onset of ASD, induces neuroinflammation and oxidative stress in the offspring and directly or indirectly damages the placenta and fetal brain during embryonic stages ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several circumstances in which a fetus may be exposed to excess testosterone, whether the source is the fetus, mother, or placenta (Baron-Cohen et al, 2015; Van De Beek et al, 2004). Congenital adrenal hyperplasia (CAH), Polycystic Ovarian Syndrome (PCOS), pre-eclampsia, and increased maternal psychological stress are conditions associated with increased androgen levels and have been associated with increased offspring risk for neurodevelopmental disorders (Davies, 2014; Gumusoglu et al, 2020; Knickmeyer and Baron-Cohen, 2006; Kumar et al, 2018; Lai et al, 2011; Li et al, 2023). Therefore, hormone dysregulation alone may be enough to induce related impairments in some, likely small, percentage of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that females with ASD show different characteristics than males with ASD. In addition, clinical studies have also reported that according to the different characteristics of ASD and camouflage, females with ASD are diagnosed much later than males with ASD [17]. Many genes are affected by risk mutations In ASD encoded proteins for synaptic, transcriptional and Chromatin remodeling pathways, which involve voltage ion channels regulating the release of action potentials, Acceleration and excitability-transcription coupling as well as histone modifying and chromatin remodeling enzymes [18].…”
Section: Discussionmentioning
confidence: 99%